Technical Support and Capacity Building for Mali-Météo: Improvement of ENACTS Datasets - Faniriantsoa, Rija; Dinh, Dannie; Dinku, Tufa (2025)
This report describes the updating of Mali National Meteorological Agency (Mali-Météo)’s ENACTS datasets through technical support and capacity building activities on ENACTS tools and products provided by The International Research Institute for Climate and Society (IRI) at Columbia University in 2025.